Pengembangan Model Pembelajaran Project Based Learning (PjBL) Berbasis Pameran Galeri Etnografi Sulawesi Selatan - Amirullah Amirullah; Fitra Widya Wati (Jambura History and Culture Journal, 2026)
This study aims to develop a Project Based Learning (PjBL) model based on the South Sulawesi ethnographic gallery exhibition in local history learning to improve students' historical thinking skills, creativity, collaboration, and cultural literacy. The study uses the Research and Development (R&D) method by adapting the Borg and Gall model, which consists of five stages: needs analysis, model design, expert validation, implementation, and evaluation. The research subjects involved 60 students of the History Education Study Program and three validators consisting of history learning experts, learning media experts, and local culture experts. Data were obtained through observation, interviews, documentation, questionnaires, and project assessments, then analyzed descriptively, qualitatively and quantitatively. The validation results showed that the developed model was categorized as very feasible to be applied in learning. The implementation model showed an increase in student active participation, communication skills, collaboration, and understanding of Bugis, Makassar, Toraja, and Mandar cultures through field observation activities and ethnographic gallery exhibitions. In addition to producing contextual learning experiences, this model also encouraged students to produce cultural documentation works in the form of ethnographic videos, cultural photography, historical posters, infographics, and local cultural miniatures. Thus, the PjBL model based on ethnographic gallery exhibitions can be an alternative innovation for local history learning in higher education.